2012
DOI: 10.1007/s11121-011-0268-8
|View full text |Cite
|
Sign up to set email alerts
|

Selling and Buying Sex: A Longitudinal Study of Risk and Protective Factors in Adolescence

Abstract: Engaging in trading sex is associated with many co-occurring problems, including elevated risk for sexually transmitted infections. Various dimensions of social support from parents, schools, and mentors may be protective against sex trading and may ameliorate the impact of risk factors. This study analyzes data from respondents to Waves I and III of the National Longitudinal Study of Adolescent Health (Add Health) who had not participated in sex trading for money or drugs in Wave I so that risk and protective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
117
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(139 citation statements)
references
References 51 publications
13
117
0
3
Order By: Relevance
“…In a study by Svensson et al (2013) as many as 78.4% of the young people who had sold sex had been exposed to sexual abuse, and 51% had been exposed to penetrating sexual abuse. In a longitudinal study by Kaestle (2012), childhood sexual abuse and running away from home stood out as critical risk factors for adolescents who had sold sex. In a study by Roe-Sepowitz (2012), emotional abuse was found to increase girls' vulnerability to prostitution and also appeared more important than experiences of childhood physical or sexual abuse.…”
Section: Socio-demographic and Psychosocial Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by Svensson et al (2013) as many as 78.4% of the young people who had sold sex had been exposed to sexual abuse, and 51% had been exposed to penetrating sexual abuse. In a longitudinal study by Kaestle (2012), childhood sexual abuse and running away from home stood out as critical risk factors for adolescents who had sold sex. In a study by Roe-Sepowitz (2012), emotional abuse was found to increase girls' vulnerability to prostitution and also appeared more important than experiences of childhood physical or sexual abuse.…”
Section: Socio-demographic and Psychosocial Healthmentioning
confidence: 99%
“…In a study by Roe-Sepowitz (2012), emotional abuse was found to increase girls' vulnerability to prostitution and also appeared more important than experiences of childhood physical or sexual abuse. Challenging background factors may help to explain why children or young people engage in risky behaviour such as running away from home (Kaestle, 2012;Pearce, 2003;Roe-Sepowitz, 2012;Roy et al, 2000;Tyler, Hoyt, Whitbeck, & Cauce, 2001), drug abuse (Nadon, Koverola, & Schludermann, 1998;Martin, Hearst, & Widome, 2010), earlier alcohol debut (Svedin & Priebe, 2007), antisocial behaviour (Svedin & Priebe, 2007), and self-harming behaviours .…”
Section: Socio-demographic and Psychosocial Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Given the risks associated with trading sex for money, understanding correlates of this behavior may have important implications for the welfare of urban African-American youth. Although, previous research has examined this issue, 8,9 most of this research has focused on runaway or street youth or youth in international settings. [10][11][12] This research has produced invaluable knowledge; however, research on trading sex for money among urban youth who have lost a parent to prison or drug addiction is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…La combinación de pobreza, abuso sexual intrafamiliar y presencia del crimen organizado, en el entorno de las adolescentes, son situaciones de alto riesgo para entrar en las redes de tráfico sexual, como revelan varios estudios (Cobbina y Oselin, 2011;Kaestle, 2012;Acharia, 2014). No es posible obtener datos precisos sobre el número de menores prostituidos/as en México; sin embargo, algunas estimaciones hablan de un intervalo que se extiende de 5 000 a 16 000 personas (Estes y col., 2008; Katsulis, 2010;Andreescu y Zaharie, 2014).…”
Section: Ciencias Socialesunclassified